The use of high‐flow nasal cannula in the pediatric emergency department - Katherine N. Slain; Steven L. Shein; Alexandre T. Rotta (Brazilian Society of Pediatrics, 2017)
Objectives: To summarize the current literature describing high‐flow nasal cannula use in children, the components and mechanisms of action of a high‐flow nasal cannula system, the appropriate clinical applications, and its role in the pediatric emergency department. Sources: A computer‐based search of PubMed/MEDLINE and Google Scholar for literature on HFNC use in children was performed. Data summary: High‐flow nasal cannula, a non‐invasive respiratory support modality, provides heated and fully humidified gas mixtures to patients via a nasal cannula interface. High‐flow nasal cannula likely supports respiration though reduced inspiratory resistance, washout of the nasopharyngeal dead space, reduced metabolic work related to gas conditioning, improved airway conductance and mucociliary clearance, and provision of low levels of positive airway pressure. Most data describing high‐flow nasal cannula use in children focuses on those with bronchiolitis, although high‐flow nasal cannula has been used in children with other respiratory disease. Introduction of high‐flow nasal cannula into clinical practice, including in the emergency department, has been associated with decreased rates of endotracheal intubation. Limited prospective interventional data suggest that high‐flow nasal cannula may be similarly efficacious as continuous positive airway pressure and more efficacious than standard oxygen therapy for some patients. Patient characteristics, such as improved tachycardia and tachypnea, have been associated with a lack of progression to endotracheal intubation. Reported adverse effects are rare. Conclusions: High‐flow nasal cannula should be considered for pediatric emergency department patients with respiratory distress not requiring immediate endotracheal intubation; prospective, pediatric emergency department‐specific trials are needed to better determine responsive patient populations, ideal high‐flow nasal cannula settings, and comparative efficacy vs. other respiratory support modalities.